Chronic Prurigo: Similar Clinical Profile and Burden Across Clinical Phenotypes - Zeidler, Claudia; Pereira, Manuel Pedro; Ständer, Sonja (Frontiers in Medicine, 2021)
Chronic prurigo is a debilitating skin disease characterized by the presence of chronic pruritus and scratching-related pruriginous lesions. The pruriginous lesions can differ in their clinics what has recently been categorized into different clinical phenotypes. The most common one is chronic nodular prurigo (syn. prurigo nodularis); other phenotypes are papular, plaque, umbilicated and linear prurigo. A comparison between these phenotypes regarding similarities and differences has not yet been performed. In this explorative analysis, itch characteristics, scratching behavior and disease burden of the nodular, papular, plaque and umbilicated prurigo were investigated in 1,128 patients. Patients with nodular and plaque prurigo were younger than patients with papular and umbilicated prurigo. The shortest duration of the underlying pruritus was found in papular and umbilicated prurigo, the longest in plaque prurigo. Itch intensity, impairment of sleep, mood and the quality of life did not differ. These findings confirm that the clinical phenotypes of chronic prurigo belong to a spectrum of one disease with similar disease characteristics and can be categorized under the umbrella term of chronic prurigo. Future clinical trials should include all phenotypes of chronic prurigo.